2004
DOI: 10.1080/08910600410017346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the consumption of heat-killedEnterococcus faecalisEC-12 preparation on microbiota and metabolic activity of the faeces in healthy adults

Abstract: The effects of the consumption (200 mg/day) of heat-killed Enterococcus faecalis EC-12 preparation (EC-12) for 14 days on microbiota and metabolic activity of the faeces were studied in eight healthy volunteers (22 Á/26 years of age). During EC-12 consumption, the counts of bifidobacteria (p B/0.05 on day 7 and p B/0.01 on day 14) were significantly increased, except for the numbers of bifidobacteria in one volunteer, whereas the counts and the frequency of occurrence of lecithinase-positive clostridia (p B/0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Terada et al [28] reported that a heat-killed strain of Enterococcus faecalis demonstrated the ability to change the human intestinal bacterial composition. It has also been shown that cell preparations altered digestive flow in an experimental animal model [29].…”
Section: Discussionmentioning
confidence: 99%
“…Terada et al [28] reported that a heat-killed strain of Enterococcus faecalis demonstrated the ability to change the human intestinal bacterial composition. It has also been shown that cell preparations altered digestive flow in an experimental animal model [29].…”
Section: Discussionmentioning
confidence: 99%
“…For this kind of substances, Mitsuoka [22] suggested the term "biogenics," which is defined as "food ingredients which beneficially affect the host by directly immunostimulating or suppressing mutagenesis, tumorigenesis, peroxidation, hypercholesterolemia, or intestinal putrefaction," and includes the administration of nonviable probiotic bacteria to obtain some "probiotic" effects [23]. Biogenic materials, including nonviable probiotic bacteria, have been actively developed as health supplements or functional foods because they possess stability to processes involving heat or acids [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction of the Ehrlich ascites tumor growth in mice was also reported [26]. In addition, it was shown that heat-inactivated Enterococcus faecalis [27] or L. gasseri [28] showed a beneficial regulatory effect in the gut. Moreover, Nakamura et al [29] found an angiotensin-I-converting enzyme (ACE) inhibitor in a Japanese sterilized milk beverage fermented by L. helveticus and Saccharomyces cerevisiae.…”
Section: The Concept Of Biogenicsmentioning
confidence: 80%